2020
DOI: 10.1111/cas.14660
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived exosomes influence the cell cycle and cell migration of human esophageal cancer cell lines

Abstract: Our laboratory previously reported the usefulness as biomarkers of exosomes in the plasma of esophageal squamous cell carcinoma (ESCC) patients. However, the influence of tumor‐derived exosomes on the tumor itself and underlying mechanisms remain unclear. We here report changes in the phenotype and gene expression when cancer cells exist in an environment with tumor‐derived exosomes. The exosomes were isolated from the culture medium of human ESCC cells (TE2, T.Tn) by ultracentrifugation; cell proliferation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 25 publications
0
20
0
2
Order By: Relevance
“…MiR-224-5p can be transferred from SW620 cells to CCD 841 CoN cells via exosomes Evidences have shown that cancer cell-derived exosomes exert a vital role in the process of malignant transformation [23,24]. In this study, exosomes were isolated from the CM of CCD 841 CoN cells and SW620 cells.…”
Section: Cmtm4 Is a Binding Target Of Mir-224-5pmentioning
confidence: 98%
“…MiR-224-5p can be transferred from SW620 cells to CCD 841 CoN cells via exosomes Evidences have shown that cancer cell-derived exosomes exert a vital role in the process of malignant transformation [23,24]. In this study, exosomes were isolated from the CM of CCD 841 CoN cells and SW620 cells.…”
Section: Cmtm4 Is a Binding Target Of Mir-224-5pmentioning
confidence: 98%
“… 19 Matsumoto et al demonstrated that tumor‐derived exosomes could promote tumor progression and malignant transformation by altering gene expression and phenotype of tumor cells. 20 ESCC cell-derived exosomes containing lncRNA prostate cancer-associated transcript 1 (PCAT1) promoted ESCC cell proliferation by sponging tumor suppressor miR-326. 21 Knockdown of PCAT1 could induce cell cycle arrest at G2/M phase, and increased paclitaxel sensitivity.…”
Section: Exosomes Regulate the Growth And Metastasis Of Ecmentioning
confidence: 99%
“…We further confirmed that these vesicles were EVs by Western blot analysis of the tetraspanin molecules CD63 and TSG101 and the non-EVs protein GM-130. We also utilized a transmission electron microscope, HT7800 (Hitachi, Tokyo, Japan) to observe EVs according to the manufacturer's instructions [44].…”
Section: Cell Evs Isolation and Identificationmentioning
confidence: 99%